Trabajo de suficiencia profesional como asesor comercial y ejecutivo de negocios de Mibanco periodo 2011 - 2018 - Aranda Leonardo, Ronald Elias (2018)
The present report of occupational sufficiency entitled WORK OF PROFESSIONAL SUFFICIENCY AS BUSINESS ADVISOR AND EXECUTIVE BUSINESS OF MIBANCO PERIOD 2011 - 2018, aims to analyze the credit system of Mibuco Trujillo agency and analyze the refinancing of credits in Financiera Confianza Trujillo agency., The following main problem was found in the system for the granting of loans, which is the increase of the delinquent portfolio and the measurement of credit risk. To solve this problem, the improvement guidelines for the measurement of credit risk in Mibanco Trujillo agency were proposed. Administration knowledge and process hierarchy were applied. The following conclusions were reached according to statistical reports of the SBS of 2015, 2016 and 2017. Mibanco has the highest percentage in small business loans of 23%, 22% and 20%; in Créditos Microempresa, 47%, 49% and 50% respectively of the Total Portfolio at the Multiple Banking Level, for which the mission and objectives directed towards microentrepreneurs are affirmed. In terms of portfolio quality in 2015, 2016 and 2017, Mibanco is below average with 4.35%, 5.47% and 6.33% in Small Business loans compared to the Total Multiple Banking Average which is 4.69%. %, 5.34% and 7.34%, due to the fact that these loans have greater control at the time of granting, in contrast to Créditos Microempresa Mibanco has representative increases of 2.68%, 3.23% and 3.97% compared to the Average of Multiple Banking that it is 2.43%, 2.69% and 3.64% because, as the amounts are smaller, the policies with which Mibanco has are more flexible, which is why it assumes greater risk.